2009
DOI: 10.1016/j.biopsych.2009.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Reduces Alcohol Self-Administration in Heavy-Drinking Smokers

Abstract: Background-Alcohol and tobacco dependence are highly comorbid disorders, with preclinical evidence suggesting a role for nicotinic acetylcholine receptors (nAChRs) in alcohol consumption. Varenicline, a partial nicotinic agonist with high affinity for the α4β2 nAChR receptor, reduced ethanol intake in rodents. We aimed to test whether varenicline would reduce alcohol consumption and alcohol craving in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
284
3
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(310 citation statements)
references
References 44 publications
16
284
3
2
Order By: Relevance
“…These data are verified in clinical tests; thus blocking these subtypes, by using varenicline, reduces the intake of alcohol in heavy drinking smokers (McKee et al 2009) and one haplotype of the 6* gene is associated with heavy alcohol use ). Furthermore, it has been shown that excessive alcohol intake in rats consuming alcohol for a long period of time causes a release of acetylcholine in the VTA followed by an increase in accumbal dopamine levels, showing that alcohol like ghrelin activates the cholinergicdopaminergic reward link (Larsson et al 2005).…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 71%
“…These data are verified in clinical tests; thus blocking these subtypes, by using varenicline, reduces the intake of alcohol in heavy drinking smokers (McKee et al 2009) and one haplotype of the 6* gene is associated with heavy alcohol use ). Furthermore, it has been shown that excessive alcohol intake in rats consuming alcohol for a long period of time causes a release of acetylcholine in the VTA followed by an increase in accumbal dopamine levels, showing that alcohol like ghrelin activates the cholinergicdopaminergic reward link (Larsson et al 2005).…”
Section: The Central Ghrelin Signalling System Integrates With a Key mentioning
confidence: 71%
“…We also showed that chlorzoxazone, an FDA-approved SK activator used for decades as a centrally acting myorelaxant, significantly reduces excessive alcohol intake in rats with intermittent access to ethanol, but does not reduce the more moderate alcohol intake in rats with continuous access to alcohol (Hopf et al, 2011). Alcohol intake in intermittent-access rats shows a number of other features, which have been considered to perhaps model some aspects of human alcoholism, including escalation of intake, sensitivity to compounds that reduce alcohol intake in human alcoholics (Steensland et al, 2007; Novel therapeutic strategies for addiction G Addolorato et al ............................................................................................................................................................... Simms et al, 2008;McKee et al, 2009) and aversion-resistant and perhaps compulsive alcohol intake (Hopf et al, 2010b). Thus, the SK activator chlorzoxazone may represent a potent and immediately accessible treatment for human alcoholism.…”
Section: Sk-type Calcium-activated Potassium Channelsmentioning
confidence: 99%
“…VAR has been broadly implicated in the reduction of reward signaling, selectively decreasing voluntary alcohol intake in both rodents (Hendrickson et al, 2010;Steensland et al, 2007) and humans (Fucito et al, 2011;McKee et al, 2009). Administration of VAR decreases subjective reports of nicotine craving (Brandon et al, 2011;Patterson et al, 2009) and smoking cue-induced activity in the medial OFC (Franklin et al, 2011) in nontreatmentseeking smokers.…”
Section: Introductionmentioning
confidence: 99%